2020
DOI: 10.1186/s12970-020-00396-z
|View full text |Cite
|
Sign up to set email alerts
|

Time-restricted eating effects on performance, immune function, and body composition in elite cyclists: a randomized controlled trial

Abstract: Background Although there is substantial interest in intermittent fasting as a dietary approach in active individuals, information regarding its effects in elite endurance athletes is currently unavailable. The present parallel randomized trial investigated the effects of a particular intermittent fasting approach, called time-restricted eating (TRE), during 4 weeks of high-level endurance training. Methods Sixteen elite under-23 cyclists were rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
103
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(115 citation statements)
references
References 52 publications
4
103
0
8
Order By: Relevance
“…The absence of significant changes could be due to the fact that the interventions in which a significant reduction in fat mass was observed were of longer duration (>12 weeks) than those used in the present study (8 weeks) [ 49 , 55 ]. Although scientific publications present evidence of changes in body composition regarding fasting as a nutritional strategy in less than 8 weeks for elite male athletes (4-weeeks) [ 56 ], an 8-week duration does not appear to be a sufficient stimulus to promote metabolic flexibility in our study population (active women). Indeed, 4 weeks for active males are not enough to improve the body composition [ 57 ], but 6 weeks was enough to find positive changes in women over 60 years [ 58 ].…”
Section: Discussionmentioning
confidence: 75%
“…The absence of significant changes could be due to the fact that the interventions in which a significant reduction in fat mass was observed were of longer duration (>12 weeks) than those used in the present study (8 weeks) [ 49 , 55 ]. Although scientific publications present evidence of changes in body composition regarding fasting as a nutritional strategy in less than 8 weeks for elite male athletes (4-weeeks) [ 56 ], an 8-week duration does not appear to be a sufficient stimulus to promote metabolic flexibility in our study population (active women). Indeed, 4 weeks for active males are not enough to improve the body composition [ 57 ], but 6 weeks was enough to find positive changes in women over 60 years [ 58 ].…”
Section: Discussionmentioning
confidence: 75%
“…Studies on IF diets and endurance capacity and performance-related parameters have produced conflicting results in endurance athletes [ 60 , 62 , 64 ]. Both R-IF and TRE studies on endurance athletes stated that IF diets had no influence on the aerobic capacity, determined by VO 2 max [ 60 , 62 , 64 ]. Additionally, one study on TT performance and R-IF in well-trained middle-distance runners showed that R-IF caused a decrease in TT performance [ 60 ].…”
Section: Popular Diets Applied To Improve Sports Performance In Enmentioning
confidence: 99%
“…However, another study determining the impact of the CHO mouth rising technique on 10 km TT performance declared that the CHO mouth rising technique provided benefits by increasing 10 km TT performance [ 64 ]. For TRE and endurance performance, Moro et al [ 62 ] revealed that a 4 week TRE had no impact on endurance performance. As for evaluating performance-related parameters, several researchers investigated the exercise-induced fatigue, blood lactate, glucose, and insulin concentrations in endurance athletes [ 61 , 63 , 64 , 65 ].…”
Section: Popular Diets Applied To Improve Sports Performance In Enmentioning
confidence: 99%
See 2 more Smart Citations